2010
DOI: 10.1097/ijg.0b013e3181c4b0c7
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Nerve Fiber Layer Thickness in Normals Measured by Spectral Domain OCT

Abstract: Normal RNFL results with SOCT are comparable to those reported with time-domain OCT. In accordance with the literature on other devices, RNFL thickness measured with SOCT was significantly correlated with age and axial length. For creating a normative database of SOCT RNFL values have to be age adjusted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
130
4
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(159 citation statements)
references
References 34 publications
22
130
4
3
Order By: Relevance
“…Refractive error and age at examination are some of the well-known confounding factors in the interpretation of peripapillary RNFL thickness. [32][33][34][35][36][37][38] In addition, we performed correlation analysis between various baseline factors and peripapillary RNFL thicknesses in multiple sectors separately. As there was a difference in the pattern of RNFL distribution according to different sectors, it would be more accurate to analyze RNFL thickness in each sector separately.…”
Section: Variablementioning
confidence: 99%
“…Refractive error and age at examination are some of the well-known confounding factors in the interpretation of peripapillary RNFL thickness. [32][33][34][35][36][37][38] In addition, we performed correlation analysis between various baseline factors and peripapillary RNFL thicknesses in multiple sectors separately. As there was a difference in the pattern of RNFL distribution according to different sectors, it would be more accurate to analyze RNFL thickness in each sector separately.…”
Section: Variablementioning
confidence: 99%
“…The light source of the SDOCT is a super luminescent diode with a wavelength of 870 nm. Infrared images and OCT scans (40,000 A-Scan/sec) of the dual laser scanning systems are acquired simultaneously (10) . Three consecutive circular B-scan (3.4-mm diameter, 768 A-scans) centered at the optic disc were performed in one visit by the same operator.…”
Section: Oct Measurementsmentioning
confidence: 99%
“…Budenz et al (2007) showed the decay per decade to be 2.0 microns. Similarly, Bendschneider et al (2010) reported the decrease in the RNFL thickness to be 1.90 microns per decade. Closer home, Mansooriet et al (2012) has also shown a negative correlation of the RNFL with age where the average RNFL thinning was 0.116 microns per year.…”
Section: Resultsmentioning
confidence: 99%
“…The mean thickness of the RNFL seen in our study was 102.64 μm which is comparable to the other studies done in other Asian countries (103.0 to 108.4 μm) (Choi et al, 2005;Hsu et al, 2008;Sony et al, 2004). However, the studies from western populations showed the mean RNFL thickness to be lower (85.8 -99.36 μm) than in Asian populations (Bendschneider et al, 2010;Bowd et al, 2000;Lopez-Pena et al, 2011). The differences in the RNFL thickness among Asians, coloured people and Western populations may have racial causes or may be dependent upon some physical phenomena.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation